Hubungan Motivasi Belajar dengan Disiplin Warga Belajar dalam Mengikuti Pelatihan Menjahit di PKBM Anarvani Kota Padang - Nindi Wirdayani; Syuraini Syuraini (RC-INSTITUT, 2020)
This research is motivated by the low level of attendance that students have in carrying out a sewing training at the Anarvani Community Learning Center in Padang. This study aims to look at the picture of students' learning motivation in carrying out sewing activities in PKBM Anarvani, see the picture of students' discipline in carrying out sewing activities at PKBM Anarvani, and can see the relationship between students' discipline and learning motivation of students. in carrying out sewing training at PKBM Anarvani. This type of research is a qualitative descriptive study. The research population was 24 people, 6 people were chosen as respondents. The type of research data is about the existence of a relationship of learning discipline with the motivation that students have in carrying out sewing training at PKBM Anarvani. A questionnaire is a technique in using data coagulation. As well as the questionnaire used as a tool used. Rank order is an analysis technique in this research. The findings in this study explain if the description of learning motivation in sewing training in PKBM Anarvani is classified as very bad, as well as the low discipline that students have when carrying out sewing training activities in PKBM Anarvani and have a link between learning motivation and student discipline when implementing sewing activities at PKBM Anarvani.